Rapid hamstring/quadriceps force capacity in male vs. female elite soccer players - Zebis, M. K.; Andersen, L. L.; Ellingsgaard, H.; Aagaard, P. (The Journal of Strength and Conditioning Research, 2011)
Knee joint injuries are a serious issue in soccer. The ability to protect the knee from injury depends largely on the strength of the hamstring relatively to the quadriceps, that is, a low hamstring/quadriceps (H/Q) strength ratio is suggested as a risk factor. Although maximal muscle strength (MVC) has often been used to evaluate the H/Q ratio, the ability to rapidly develop force (rate of force development [RFD]) is more relevant in relation to fast dynamic movements. The aim of this study was to introduce and investigate a rapid RFD H/Q strength ratio compared with the traditional MVC H/Q strength ratio in elite soccer players. Twenty-three elite soccer players (11 women, 12 men) performed maximal voluntary static contraction for the hamstring and quadriceps in an isokinetic dynamometer, from which the maximal muscles strength (MVC) and RFD were extracted. Test-retest reliability for the RFD H/Q ratio was high (intraclass correlation coefficient = 0.664-0.933). The initial contraction phase up to 50 milliseconds from the onset of contraction showed a low RFD H/Q ratio compared to the MVC H/Q ratio (p < 0.001). These results suggest a reduced potential for knee joint stabilization during the very initial phase of muscle contraction. Two female players—both with a markedly low RFD H/Q ratio, but a normal MVC H/Q ratio, compared with the group mean—sustained ACL rupture at a later occasion. The high reliability of the new RFD H/Q strength ratio indicates that the method is a relevant tool in standardized clinical evaluation of the knee joint agonist-antagonist relationship.